Major transcriptional changes observed in the Fulani, an ethnic group less susceptible to malaria - Quin, Jaclyn E; Bujila, Ioana; Chérif, Mariama; Sanou, Guillaume S; Qu, Ying; Vafa Homann, Manijeh; Rolicka, Anna; Sirima, Sodiomon B; O'Connell, Mary A; Lennartsson, Andreas; Troye-Blomberg, Marita; Nebie, Issa; et al. (eLife, 2017)
The Fulani ethnic group has relatively better protection from Plasmodium falciparum malaria, as reflected by fewer symptomatic cases of malaria, lower infection rates, and lower parasite densities compared to sympatric ethnic groups. However, the basis for this lower susceptibility to malaria by the Fulani is unknown. The incidence of classic malaria resistance genes are lower in the Fulani than in other sympatric ethnic populations, and targeted SNP analyses of other candidate genes involved in the immune response to malaria have not been able to account for the observed difference in the Fulani susceptibility to P.falciparum. Therefore, we have performed a pilot study to examine global transcription and DNA methylation patterns in specific immune cell populations in the Fulani to elucidate the mechanisms that confer the lower susceptibility to P.falciparum malaria. When we compared uninfected and infected Fulani individuals, in contrast to uninfected and infected individuals from the sympatric ethnic group Mossi, we observed a key difference: a strong transcriptional response was only detected in the monocyte fraction of the Fulani, where over 1000 genes were significantly differentially expressed upon P.falciparum infection.
Keywords: Monocytes; monocyty; Ethnicity; Cells, Cultured; Pilot Projects; Humans; DNA Methylation; metylace DNA; Malaria, Falciparum; Transcription, Genetic; etnicita; kultivované buňky; Disease Resistance; stanovení celkové genové exprese; lidé; Gene Expression Profiling; pilotní projekty; tropická malárie; odolnost vůči nemocem; genetická transkripce